MENGATASI KESULITAN BELAJAR DENGAN MEMAHAMI GAYA BELAJAR - Ahmad Sukartawan (CONS-IEDU, 2022)
In the educational process, each individual has their own learning style. Learning style can be said to be a person's tendency to adapt a certain learning strategy by searching and trying. This method differs from one student to another. An appropriate learning style is the key to success for a student in learning and overcoming learning difficulties in students. The focus of this research lies in how to overcome students' learning difficulties by knowing students' learning styles. In knowing learning styles, researchers used Visual, Audio and Kinesthetic (VAK) approaches, and Multiple Intelligence. The research used a descriptive qualitative approach. This research was conducted in a natural setting at MA Al-Ahsan Bareng Jombang. The data was taken by way of the researchers going directly to MIN 2 Jembrana Bali. Data were collected through interviews, observing the teaching and learning process and other documentation that supports the data collection process. The main objective is to systematically describe the facts and characteristics of the object or subject being studied accurately. With the hope of being a contribution in the world of education. Especially related to overcoming student learning difficulties. In knowing student learning styles, teachers at MIN 2 Jembrana Bali do not use certain theories but combine several theories such and Multiple Intelligences (multiple intelligences). Teachers still use the old model of learning strategies and do not rely on students' learning styles. Al-Ahsan student learning difficulties because the learning process does not pay attention to learning styles. Based on the findings, the researchers suggest: (1) In order for the learning process to run effectively and be followed by students, teachers need to recognize student learning styles, (2) madrasas need to collaborate with other parties who have the ability to carry out assessments related to student learning styles, (3) Madrasahs need to equip teachers with practical knowledge and skills regarding student learning styles, and (4) Guidance Counseling (BK) teachers need to facilitate the introduction of students' learning styles